2017
DOI: 10.1160/th16-08-0606
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive expression signatures of serum microRNAs in ischaemic stroke and transient ischaemic attack patients

Abstract: Circulating microRNAs (miRNAs) have recently emerged as promising biomarkers for ischaemic stroke (IS). However, the expression patterns of specific miRNAs in transient ischaemic attack (TIA) patients have not been investigated. Their predictive values for the presence of IS and TIA and their relationships to the neurological deficit severity of IS and the subsequent stroke risk after TIA remain unclear exactly. In this study, 754 miRNAs were initially screened by the TaqMan Low Density Array (TLDA) in two poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Logistic regression and ROC curve analyses showed that these changed miRNAs may function as predictive and discriminative biomarkers for IS and TIA. Thus, authors suggested that, their distinctive expression signatures may contribute to assessing neurological deficit severity of IS and subsequent stroke risk after TIA [78].…”
Section: Circulating Mirnas and Strokementioning
confidence: 99%
“…Logistic regression and ROC curve analyses showed that these changed miRNAs may function as predictive and discriminative biomarkers for IS and TIA. Thus, authors suggested that, their distinctive expression signatures may contribute to assessing neurological deficit severity of IS and subsequent stroke risk after TIA [78].…”
Section: Circulating Mirnas and Strokementioning
confidence: 99%
“…This temporal expression pattern might be useful in elucidating the mechanism of miRNA involvement in the pathophysiology and pathogenesis of acute ischemic stroke. An elevation of serum miRNA in the acute phase of ischemic stroke is possibly due to the passive release from ischemia-vulnerable neurons [ 12 ] or by active secretion via extracellular vesicles [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence indicating that ischemic stroke is caused by intracranial thrombosis or extracranial embolism, resulting in a lack of blood flow and supply of oxygen and nutrients ( 4 , 19 , 31 ). Subsequently, multiple complex factors lead to the destruction of the blood-brain barrier following ischemic stroke, which further aggravates brain damage and a series of neurological events, including oxidative stress, toxicity of excitatory amino acids, excessively high calcium ion concentrations and increased apoptosis ( 4 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that miR-181a-5p levels were significantly increased in the serum of patients with ischemic stroke ( 18 ). However, few studies have been conducted on the role of miR-181a-5p in ischemic stroke and its regulatory mechanism ( 19 ). It has been demonstrated that a lncRNA, small nucleolar RNA host gene 12 (SNHG12), serves a critical role in ischemic stroke by acting as a ceRNA and competing with various miRNAs to regulate specific RNA transcription ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%